Implementation of Ferry Parking Management System Using Python-Based Stack Method - Susilowati, Susi (IJISTECH (International Journal of Information System and Technology), 2024)
Organizing car parking inside ships presents a logistical challenge that requires effective solutions to maximize space utilization and facilitate the entry and exit of vehicles. This study explores the implementation of stack data structures in a car parking system inside ships. The stack method is chosen due to its LIFO (Last In, First Out) characteristics, which are suitable for situations where the last vehicle to enter is the first to exit, optimizing vehicle flow when the ship docks. The system is designed using stack algorithms to arrange the parking position of each vehicle, minimizing the time and space required for maneuvers. Simulation results show that the stack implementation improves parking efficiency by up to 30% compared to conventional methods. Additionally, this system can reduce vehicle wait times for exiting by up to 25%. This implementation also considers the safety and stability factors of the ship by balancing the distribution of vehicle weights. Therefore, this study concludes that the use of stack data structures in organizing car parking inside ships can enhance operational efficiency and maximize parking capacity.